Designing STEM activities on making battery from household chemical substances for grade 12 students - ตรีเดชา, กนกวรรณ; วรรณประภา, ธนะวัฒน์; ตั้งเตรียมจิตมั่น, นภา (Progress in Applied Science and Technology, 2019)
This research aimed to create a STEM activity on making battery from household chemical substances and to study the engineering design process and scientific skills of grade 12 students after attending this activity. The participants were selected from the second semester students in science program of 2018 academic year. They were 41 students who joined the electrochemistry science club. The research model was One Group Posttest Design, compared to 80 percent criteria. The research tools included a lesson plan, an evaluation form for instructors to evaluate engineering design process of students and the test questions for students to evaluate their fourteen scientific skills. The results showed that students gained a very good engineering design process with 90.4%. Scientific skills of students were also high as 83.4% after attending this activity.